Hasil Perbandingan Sistem Pemerintahan Menurut UUD 1945 Dengan Hasil Perubahan Setelah Amandemen - Anthony Sutedja; Wilma Silalahi (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
The system of government is an essential element in the continuity and existence of a state. Every country inevitably has its own system of government, which may differ from that of other nations. The freedom to determine a system of government must not involve interference or intervention from other countries, as each state has the right to establish and implement its own system. In Indonesia, the administration of government since independence has undergone several changes up to the present day. These changes are referred to as amendments. The amendments to the Constitution concerning the system of government were carried out four times, between 1999 and 2002. These changes were based on government policies and, once again, were not the result of coercion, demands, or pressure from other countries. Rather, they were undertaken by the Indonesian government to ensure the continuity of the state, safeguard national sovereignty, and, most importantly, to promote the welfare of the Indonesian people. In the process of altering a system of government, debates and differing opinions inevitably arise. Therefore, deliberation and public consultation are necessary. The government must carefully evaluate and analyze the inputs from the people before making decisions and implementing them in Indonesia. The government, in principle, does not enact changes or policies solely on its own will without considering public opinion, except in urgent circumstances that require immediate action. Fundamentally, Indonesia adheres to a democratic system of government, in which democracy is defined as a form of governance where the highest authority resides in the hands of the people.